A Safe Place To Go? A Descriptive Study of Safety Strategies Among College Female Students. (June 2017) - Zedaker, Sara; Muftić, Lisa R.
Safety planning, simply put, is a detailed, personalized, and practical plan that is created to protect oneself against an abusive (or potentially abusive) partner. Relying on self-reported data from an online survey of female college students from a state university in Texas, this study focuses on safety strategies centered around escape planning (e.g., whether or not students have a safe place to go, where they would go, and what they would take with them) as well as what factors influence this (e.g., prior experiences with intimate partner violence). Using bivariate analyses to determine any association between factors that influence various aspects of the safety planning process, a number of important findings are reported. The majority of students indicated that they had a safe place to go and this was most likely to be a family or friend's residence. Additionally, most students noted that they would take what is typically discussed in safety planning strategies (e.g., money, cellular phone, keys, identification, and clothing). Students who reported lower levels of social support and prior exposure to parental domestic violence were more likely to report they did not have a safe place to go. These findings underscore the importance of expanding violence prevention activities on college campuses beyond sexual assault, with information provided to all students on safety planning.